Flow inside axial pump impellers - Resnick, Avi (Cranfield University, 1982)
The subject of this work is the flow inside an axial pump impeller, which is studied both numerically and experimentally. The aim of the work is to provide a numerical method to predict the three-dimensional flow field within an axial flow pump impeller. The numerical scheme is divided into three basic parts. The first part involves the matrix through flow method to obtain the mainstream flow profiles on various blade-to-blade stream surfaces distributed from hub to tip and for given boundary conditions. In addition these solutions w to obtain a detailed flow field in the region of the leading edge. Furthermore, the transport equations of vorticity are integrated along each streamline to obtain the normal and stream wise components of vorticity.